Absence of mothers of children under one year in the growth and development program - Silva Fhon, Jack Roberto (2017)
OBJECTIVES: Identify factors that influence the absence of mothers of children under one year in the growth and development program in the Health Center. MATERIAL AND METHODS: Quantitative, descriptive cross sectional study with 117 mothers of children under one year between July and November 2012. For data collection, we used demographic profile and absence factors to the program with accessibility to health center and the growth and development program (GDP), Quality of attention and Information. We used descriptive statistic with measures of central tendency, dispersion and frequency. RESULTS: In the Accessibility to the Health Center domain, more than half didn’t have any difficulty to access and they transported by motorcycle, and the travel time was 11,66 minutes. In relation to GDP program, the absence was due lack of time, the time was inadequate and the attention time was over an hour. The Quality of attention domain, the mothers said that it was good to very good for the administrative and nursing staff. In the Information domain, the nurse did continue educated to the mothers’ absence. CONCLUSIONS: There are external and institutional factors that the mother didn’t have an adequate adhesion to the GDP program. It´s important to create some strategies to reverse this situation.